Sufism : a new history of Islamic mysticism - Knysh, Alexander Alexander D. Knysh (Princeton University Press, 2017)
A path-breaking history of Sufism, from the earliest centuries of Islam to the present after centuries as the most important ascetic-mystical strand of Islam, Sufism saw a sharp decline in the twentieth century, only to experience a stunning revival in recent decades. In this comprehensive new history of Sufism from the earliest centuries of Islam to today, Alexander knysh, a leading expert on the subject, reveals the tradition in all its richness. Knysh explores how Sufism has been viewed by both insiders and outsiders since its inception. He examines the key aspects of Sufism, from definitions and discourses to leadership, institutions, and practices